Using natural convection mechanism of nanofluid for cooling an embedded hot plate in corner of a square enclosure: A numerical simulation. (May 2022) - Cao, Yan; Mansir, Ibrahim B.; Mouldi, Abir; Gepreel, Khaled A.; Dahari, M.; Le, Tri Hieu; Badran, Mohamed Fathy; Nguyen, Van Nhanh; Wae-hayee, Makatar
Abstract: Cooling is one of the most important issues for thermal engineers, and the use of simple and inexpensive methods greatly contributes to the efficiency of a thermal system. Also, in recent decades, the development of numerical methods and the advent of computers has led to the emergence of computer simulations. In present numerical study, the natural convection mechanism of nanofluid based on water and titanium oxide ( T i O 2 ) were simulated by computational fluid dynamics (CFD) to cool a hot inclined plate inside a square chamber. The considerable innovation in this study is the nanofluids properties depending on temperature, nanoparticle diameter and volume fraction and the cavity is able to incline. The impacts of two Rayleigh numbers ( 10 2 ≤ R a ≤ 10 4 ), four volume fractions ( 0 ≤ φ ≤ 0.06 ) and four inclined angles ( 0 ≤ γ ≤ 45 ) were analyzed on the average convective heat transfer coefficient. This study briefly demonstrated that the optimum values of volume fraction for Rayleigh numbers 10 2 a n d 10 4 were 0.06 and 0.02, respectively. Moreover, increasing the volume fraction to 6% in low Reynolds number improved the average convective heat transfer coefficient by 21%.